An Overview in Disadvantages of the Modern Communications - Jasim, Hasan Bakheet (New Insights into Physical Science Vol. 13, 2021)
In modern societies, social networking and many more, are making human life easier. Communication and technology are created many changes in all fields of life. High speed in, translations, transport, shorten the time, exchange the information between the people, and others cases. Communication can be define as a process in which individuals share their opinion, ideas and various information by means of several such as writing, reading, symbols, signs, speech and communication. We review and discussed the reasons and results for bad (disadvantage) for the communications in Iraq. Most of the companies for communications and networks in Iraq are using the old and worst methods to connectedness in communications. After the year 2003, all people are looking forward or willing to use and live the modern life, by using the information technology (IT), but they are not thought or (forget), what happened to them, when they are used worst connectedness the networks. The goal for this study to investigation all aspects of life, where more important for people life as, (health, economy side, the cost, security, maintenance, manufacture high-quality, services network, week internet (wobbling), banks, kid card cards or master card, stack the internet pack, laser planning for life, power outages and irregularity during the day, the environmental pollution). All these are affected on the life. We found increase in, more diseases are founded, Cancer disease, Congenital malformations, Abnormal birth(giving birth before her time), Hair loss, increased respiratory infections, increased skin allergies, skin spots, the drawer dose is high because near the radiation source. In additional to the problem of the age is the environmental pollution is not controlled in all the developed and undeveloped countries of the world and it directly affects people lives. So the IT revolution has become more affected than the useful. Emphasizing the inevitability and security of the information sent and how they stolen it by the hackers through the development of programs.